DC Home Appliances for DC Distribution System - MUHAMMAD KAMRAN; MUHAMMAD BILAL; MUHAMMAD MUDASSAR (Mehran University Research Journal of Engineering and Technology, 2017)
This paper strengthens the idea of DC distribution system for DC microgrid consisting of a building of 50 apartments. Since the war of currents AC system has been dominant because of the paucity of research in the protection of the DC system. Now with the advance research in power electronics material and components, generation of electricity is inherently DC as by solar PV, fuel cell and thermoelectric generator that eliminates the rectification process. Transformers are replaced by the power electronics buck-boost converters. DC circuit breakers have solved the protection problems for both DC transmission and distribution system. In this paper 308V DC microgrid is proposed and home appliances (DC internal) are modified to operate on 48V DC from DC distribution line. Instead of using universal and induction motors in rotary appliances, BLDC (Brushless DC) motors are proposed that are highly efficient with minimum electro-mechanical and no commutation losses. Proposed DC system reduces the power conversion stages, hence diminishes the associated power losses and standby losses that boost the overall system efficiency. So in view of all this a conventional AC system can be replaced by a DC system that has many advantages by cost as well as by performance